2020
DOI: 10.1016/j.celrep.2019.12.078
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacillus subtilis Protects against α-Synuclein Aggregation in C. elegans

Abstract: Highlights d B. subtilis PXN21 inhibits and reverses a-syn aggregation in a C. elegans model d Spores and vegetative cells protect through different mechanisms d The probiotic inhibits a-syn aggregation by changing the host sphingolipid metabolism d Biofilm formation in the gut and bacterial metabolites reduce a-syn aggregation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 110 publications
4
86
0
Order By: Relevance
“…Also important for the probiotic effectiveness, B subtilis is able to form robust and long-lasting biofilms (ie, biopellicle) in the gut environment, a physiological property (absent in most LAB) that has been reported as crucial for the production of the beneficial effects of probiotic B subtilis on eukaryotic host. [14][15][16][17] Here, we presented two cases of type 2 diabetes mellitus in obese patients with poor control of the disease. Obesity is a strong risk factor for diabetes onset and progression.…”
Section: Discussionmentioning
confidence: 93%
“…Also important for the probiotic effectiveness, B subtilis is able to form robust and long-lasting biofilms (ie, biopellicle) in the gut environment, a physiological property (absent in most LAB) that has been reported as crucial for the production of the beneficial effects of probiotic B subtilis on eukaryotic host. [14][15][16][17] Here, we presented two cases of type 2 diabetes mellitus in obese patients with poor control of the disease. Obesity is a strong risk factor for diabetes onset and progression.…”
Section: Discussionmentioning
confidence: 93%
“…Otherwise, LABs would perish upon exposure to the acidic pH of the stomach and the microbicide action of intestinal bile (Yahav et al, 2018). More recently, it has been shown in animal models that the B. subtilis biofilm is important in delaying neurodegenerative diseases (i.e., Alzheimer's and Parkinson's diseases) (Cogliati et al, 2019;Goya et al, 2020). Therefore, the importance of B. subtilis biofilm in basic and applied research cannot be questioned.…”
Section: New Role For the Transcription Factor Sigb In Biofilm Growthmentioning
confidence: 99%
“…Indeed, a recent study reported that probiotic treatment inhibited alpha-synuclein aggregation and facilitated aggregate clearance in a Caenorhabditis elegans model of synucleinopathy thus suggesting gut microbiota modulation as a potential therapy in PD. 58 …”
Section: Introductionmentioning
confidence: 99%